2010
DOI: 10.2320/matertrans.m2010040
|View full text |Cite
|
Sign up to set email alerts
|

Microstructures of Zr-Added Co-Cr-Mo Alloy Compacts Fabricated with a Metal Injection Molding Process and Their Metal Release in 1 mass% Lactic Acid

Abstract: The microstructures of Zr-added Co-29Cr-6Mo alloy compacts fabricated with a metal injection molding (MIM) process and their metal release from the compacts immersed in 1% lactic acid were investigated for medical applications. The relationship between the microstructure and amount of Co released from the compacts is discussed phenomenologically. The relative density of the Co-29Cr-6Mo compacts increased when Zr was added to the powder with amounts of 0.03 and 0.1 mass% and sintered in Ar or N 2 . The amounts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
1
3
1
Order By: Relevance
“…Several previous studies demonstrate that a small additions of Zr to Co–Cr–Mo alloys decrease metal ion release in vitro . However, in the present study, no significant differences in eluted metal ion concentrations were observed between ultralow‐Ni Co–Cr–Mo and ultralow‐Ni Co–Cr–Mo with Zr implanted mice tissues, potentially reflecting insufficient quantities of implanted metals and/or insufficient Ni contents of these new alloys.…”
Section: Discussioncontrasting
confidence: 77%
“…Several previous studies demonstrate that a small additions of Zr to Co–Cr–Mo alloys decrease metal ion release in vitro . However, in the present study, no significant differences in eluted metal ion concentrations were observed between ultralow‐Ni Co–Cr–Mo and ultralow‐Ni Co–Cr–Mo with Zr implanted mice tissues, potentially reflecting insufficient quantities of implanted metals and/or insufficient Ni contents of these new alloys.…”
Section: Discussioncontrasting
confidence: 77%
“…Therefore the low injection pressure in this study was attributed to ZrO 2 particles, similar to another study [43]. This mechanism has also been observed in the injection moulding of other materials containing fine and spherical refractory like ZrO 2 particles [38,4446]. Therefore, adding fina and spherical ZrO 2 particles to 17-4 PH feedstock, in addition to thermal stabiliser have also properties that make low injection pressure to fill the mould cavity.…”
Section: Resultssupporting
confidence: 84%
“…Meanwhile, the formation of Inconel 718 nickel-base superalloy is mainly by taking Ni element as the base for dissolution with the addition of many solid solution elements dominated by Fe and Cr during dissolution, followed by the addition of Nb, Al, and Ti-dominated trace strengthening elements to solid solution for precipitation strengthening through aging . Considering that the atomic radius of Ni, Cr and Fe are similar ( R Ni : 0.124 nm, R Cr : 0.127 nm and R Fe : 0.127 nm), it is found by combining the solubility criterion of solid solution , that the elements Cr and Fe take the lead in forming unlimited solid solution with substitution characteristic in Ni base, and the impact of elastic strain caused by different atomic sizes on the atomic distribution in the solid solution alloy can be neglected, so the nearest-neighbor distribution between atoms in Ni–Cr–Fe solid solution alloy is mainly determined by the chemical action between elements (i.e., the enthalpy of mixing). Therefore, this paper puts forward first taking the element Ni matrix as basis to study the method of building short-range order cluster model of three-component solid solution with the introduction of massive solid-solution elements (Fe and Cr), and then based on the above model, studying the short-range order cluster model of six-component solid solution after introducing the trace strengthening elements (Nb, Al and Ti), so as to accurately characterize the solid solution state of Inconel 718 nickel-base superalloy.…”
Section: Short-range Cluster Order Model Building Of Multicomponent A...mentioning
confidence: 99%